Fatigue Evaluation of Steel Truss Arch Bridge Based on Traffic Load Simulation Using Weigh-in-Motion Data: Case Study of Rumpiang Bridge - Rio Pramana; Ivan Sandi Darma (Directorate for Research and Community Services, Institut Teknologi Bandung, 2024)
The aim of this study was to evaluate the fatigue life of Rumpiang Bridge in Barito Kuala Regency, South Kalimantan, which features a 200-meter-long steel truss arch structure. Fatigue evaluation was performed by referencing the AASHTO Manual for Bridge Evaluation 2018 and the provisions in RSNI T-03-2005 and using the cumulative fatigue damage method. Actual traffic loads based on weigh-in-motion (WIM) data obtained from Prof. Dr. Ir. Sutami Road in Lebak Regency, Banten over a seven-day period were simulated using structural modeling in MIDAS Civil 2022. The results indicated that Rumpiang Bridge is susceptible to fatigue failure, due to a cross-girder element experiencing a maximum stress range of 171.30 MPa and an effective stress range of 75.31 MPa. The current accumulated fatigue damage is 0.179, with an estimated remaining fatigue life of 16 years. This relatively short remaining life is primarily due to 35.02% of vehicles recorded in the WIM data being overloaded. Implementation of traffic restrictions can extend the fatigue life of the bridge. After conducting various weight restriction scenarios, it was found that a restriction with a maximum vehicle load of 26 tons would result in a fatigue life that exceeds the design life of the bridge.